BES1/BZR1 Homolog 3 cooperates with E3 ligase AtRZF1 to regulate osmotic stress and brassinosteroid responses in Arabidopsis. (10th October 2020) - Van Nguyen, Tinh; Park, Cho-Rong; Lee, Kyeong-Hwan; Lee, Sungbeom; Kim, Cheol Soo
Abstract : BEH3, a negative regulator of osmotic stress is linked to the BR signaling response through a BEH3-AtRZF1 coordinated pathway in Arabidopsis. Abstract: Proline (Pro) metabolism plays important roles in protein synthesis, redox balance, and abiotic stress response. However, it is not known if cross-talk occurs between proline and brassinosteroid (BR) signaling pathways. Here, an Arabidopsis intergenic enhancer double mutant, namely proline content alterative 41 ( pca41 ), was generated by inserting a T-DNA tag in the Arabidopsis thaliana ring zinc finger 1 ( atrzf1 ) mutant background. pca41 had a T-DNA inserted at the site of the gene encoding BES1/BZR1 Homolog 3 (BEH3). pca41 has a drought-insensitive phenotype that is stronger than atrzf1 under osmotic stress, including high Pro accumulation and decreased amounts of reactive oxygen species. Analysis of physiological, genetic, and molecular networks revealed that negative regulation of BEH3 during abiotic stress was linked to the BR signaling pathway. Our data also suggest that AtRZF1, an E3 ubiquitin ligase, might control osmotic stress, abscisic acid, and BR responses in a BEH3-dependent manner. Under darkness, pca41 displays a long hypocotyl phenotype, which is similar to atrzf1 and beh3, suggesting that BEH3 acts in the same pathway as AtRZF1. Overexpression of BEH3 results in an osmotic stress-sensitive phenotype, which is reversed by exogenous BR application. Taken together, our results indicate that AtRZF1 and BEH3 may play important roles in the osmotic stress response via ubiquitination and BR signaling.